Titulación “Actualización del Manual de Funciones y Descripción de Cargos por Competencias del Talento Humano de ELEPCO S.A.” - Heredia, Martina (2021)
This research aimed to update the manual of functions and classify positions by competencies in Empresa Eléctrica Cotopaxi S.A. to solve the duplicity of functions and classify them according to each employee's competencies in the administrative area. The method used in the research is qualitative because the skills, knowledge, competencies, and primary functions were investigated. It was applied an interview to managers of different departments in the administrative area as an instrument for collecting information. The results obtained through the analysis of the instrument is that not all employees know functions to perform in the job. In addition, it served as raw material for the proposal to update the manual of functions and classification of positions by competencies of the administrative area. It allowed collaborators to take into account the functions to be performed in their respective jobs, and with the technical and behavioral competencies that are reflected in the manual of functions according to the dictionary of labor competencies, the template of the job profile granted by the Ministry of Labor and proposed by the researcher will comply. It is recommended that the municipality update the manual of functions and job classification every year to reduce conflicts in work due to duplication of functions.